Consumer Socialization Process and Adolescent Junk Food Consumption in Chennai and Hyderabad - Jayanthi, B. V.; Hari Prasad Reddy, Y. (Indian Journal of Marketing, 2017)
Generally, socialization can be described as the process whereby a kid eventually becomes a more or less perfect member of a society in all respects and acquires the skills necessary to function amid the culture in which he/she is born and begins to grow. For a child, the drivers or the factors behindÂ his/her behaviour include his/her own family and the members who interact with him/her. This socialization process leads to many merits and demerits in a child’s life. One of the most serious demerits is the consumption pattern of the child which is influenced by his/her surrounding environment. The world today is witnessing childhood obesity rate, which is rising every year at an alarming pace. The habit of eating junk food (which is one large source of fat which accumulates in the body) has increased over the years, also contributing to the obesity issue. This study, conducted during 2011 to 2013, attempted to find out the reasons that could be attributed to the increasing level of childhood obesity in the cities of Chennai and Hyderabad, and the role of persuasive marketing in aggravating the issue. This article defined those reasons as motivational perception factors, that is to say, the elements which motivate the children to consume certain things about which they have their own perceptions.